Agama dan Matlamat Pembangunan Lestari (SDGs): Peranan Rumah Ibadat dalam Kebajikan Masyarakat: Religion and Sustainable Development Goals (SDGs): The Role of Houses of Worship in Social Welfare - Mohd Khalli, Mohd Nazmi; Mohd Sharif, Mohd Farid; Mat Akhir, Noor Shakirah; Abu Bakar, Norsofiah; Chow , Yean Fun; Sumari, Putra (Afkar: Jurnal Akidah dan Pemikiran Islam, 2024)
The issue of social welfare has become a global concern, as neglecting it can threaten human life. As a result, this concern led to the creation of a global declaration through the Sustainable Development Goals (SDGs), which outlines the desire for mutual peace for the welfare of society. In this context, religion is seen as having the potential to sustain social welfare in the long term. This study discusses the role of religion through cooperative practices by Islamic and non-Islamic houses of worship in social welfare. The research method employs descriptive textual analysis based on literature findings, focusing on four religions—Islam, Christianity, Buddhism, and Hinduism—along with their places of worship, such as mosques, churches, temples, and shrines. The study presents the religious perspectives and the history of places of worship in managing social welfare. Generally, these four religions emphasize the importance of social welfare. Therefore, the houses of worship in these religions expand their roles, not only as centers of worship but also as spaces for the community to access welfare. These findings are supported not only by religious sources but also by historical records, which show that the cooperation between places of worship can continuously elevate social welfare. Thus, this study contributes to the field by advocating for houses of worship as welfare institutions for the benefit of society.